MODERN FUNDAMENTALS OF ENZYME IMMUNOASSAY - Umarova Tamila Abdufattoevna; Kudratova Zebo Erkinovna; Narzullayev Qamariddin Xamdam ogli (Web of Journals Publishing, 2024)
Enzyme-linked immunosorbent assay (ELISA) is a laboratory immunological method for the qualitative or quantitative determination of various low molecular weight compounds, macromolecules, viruses, etc., based on the specific reaction of antigens (AG) with antibodies (AT). The detection of the resulting complex is performed using an enzyme as a label to visualize the reaction.
Keywords: antigen, antibodies, biological fluid, enzyme immunoassay, viruses, bacteria.